FACTORS AFFECTING THE DELAY OF DECISION MAKING TO RECEIVE HEALTH SERVICES IN PREECLAMPSIA PREGNANT MOTHERS AT RSUD MGR GABRIEL MANEK SVD ATAMBUA - Monika Mongang Manuk; Muhammad Ilham Aldika Akbar; Ivon Diah Wittiarika (UNIVERSITAS AIRLANGGA, 2021)
AbstractBackground: Preeclampsia is one of the risk factors for complications and also contributes to the high rate of morbidity and mortality in mothers and babies. The Maternal Mortality Rate (MMR) at the Mgr. Gabriel Manek Hospital, SVD Atambua has continued to increase in the last three years, from 2017 to 2019. It was recorded that in 2019 there were 126 cases of severe preeclampsia and eclampsia with 5 cases of maternal death and 2 maternal causes of death. is eclampsia. In addition to the factors that cause maternal death, one of the contributing causes of maternal and infant mortality is caused by the speed at which decisions are made in the family. Pregnant women are at risk of experiencing maternal death if during the referral process they experience at least one of the three delays, namely being late in making the decision to be referred. This study aims to determine the factors that influence the delay in decision making in preeclampsia pregnant women. Methods: The type of research is observational analytic with a cross sectional design. Collecting data using primary data with a questionnaire instrument by interview and secondary data obtained from the register of maternity mothers and medical records. The number of samples is 30 respondents. The sampling technique used was total sampling. The data were processed and calculated using frequency tables and cross tabulations and then analyzed using Multiple Logistics Regression Analysis with a significance level of 5% (p = 0.05). Bivariate data analysis used fisher's exact test andtest cramer's v. Results: The results showed that the factors that caused delays in decision making were knowledge having a p-value of 0.006 (OR 2.293, 95% Cl: 0.481-10.918), confidence having a p-value of 95%: 0.002-0.513, health insurance having p-value 0.010 (OR 0.000, 95% Cl: 0.000). Multivariate analysis shows that work is the most dominant factor in delaying decision making compared to other factors, and it can be concluded that the more working mothers, the smaller the delay, and the more mothers who do not work, the greater the delay in making decisions to get health services. . Conclusion: There is a relationship between knowledge, belief, occupation, and health insurance on the delay in decision making.